Incidental Vs Intentional Verbal Learning in Aurally Handicapped Children - Lal KK (Journal of All India Institute of Speech and Hearing, 1970)
Man is primarily a verbal learner, when an individual or subject enters the laboratory, he already possesses a rich repertory of verbal responses, which is well over learned and highly organized. For this reason, it has been difficult to find standardized materials for the study of verbal learning faced with verbal materials. Each subject has his own complex of association meanings and pre- ferences in relation to that material.